A Survey of sustainable development : social and economic dimensions - Harris, Jonathan M. (Frontier issues in economic thought, 2001)
Summaries of essays on sustainable human and economic development. Topics include: Population and the demographic transition; Agriculture and renewal resources; Energy and materials use; Globalization and corporate responsibility; Local and national strategies.